PENGARUH CORPORATE GOVERNANCE TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Uun Sunarsih; Puput Handayani (Universitas Katolik Indonesia Atma Jaya, 2018)
The purpose of this study is to examine the effect of corporate governance on tax avoidance in manufacturing companies listed on the Stock Exchange in 2012-2015. The method used was purposive sampling and obtained eleven companies. Secondary data is obtained through www.idx.co.id and www.sahamok.com. The results of this study indicate that institutional ownership has no effect, meaning that the small size of institutional ownership has not been able to become an effective monitoring tool in reducing tax avoidance. Managerial ownership has influence. This means that managerial ownership has effectively monitored the company. The independent board of directors is influential. This means that the proportion of independent commissioners has a good performance, which can reduce tax avoidance. The audit committee has no effect. This is possible because it is not able to increase supervision of management due to limited authority. Influential audit quality. This means that the company audited by KAP The Big Four will be more trusted by the tax authorities because it has high work integrity. Executive compensation has no effect. This is possible because of the high compensation received by the executive has not been able to bridge the difference of interests between shareholders and managers.